Latent profile analysis of burnout, depression, and anxiety symptoms among Chinese medical staff with frontline anti-epidemic experience in the post-COVID-19 pandemic era - Xu, Huachun; Qiu, Lanjun; Chen, Yu; Zhang, Mengjun; Li, Junyi; Xiang, Guochun (Frontiers in Public Health, 2025)
BackgroundFrontline medical staff’s psychological symptoms deserve persistent attention after 3 years of high-pressure and high-intensity work during the pandemic. In addition, the meaning of burnout and its relationship with depression and anxiety have long been debated. This study aimed to identify profiles of these symptoms among Chinese medical staff with frontline anti-epidemic experience, along with their distinguishing characteristics.MethodsPsychological symptoms of burnout (exhaustion, cynicism, and inefficacy), depression, and anxiety from 989 doctors and 1,105 nurses were explored with latent profile analysis. The R3step method was conducted to analyze the predictive factors of those medical staff’s symptoms.ResultsThree symptom profiles were identified for medical staff, with high-level (62.1%), moderate-level (28.9%), and low-level symptoms (9.0%). In the low-level and moderate-level profiles, symptom variables considered had a consistent trend. However, within the high-level profile, the inefficacy of burnout remained at a lower level, and anxiety performed as the most prominent symptom. Variables of gender, age, salary satisfaction, work hours, and work intensity predicted medical staff profiles (p < 0.05).ConclusionIn the post-COVID-19 era, former frontline Chinese medical staff’s psychological symptoms were divided into three latent profiles. Symptoms of burnout, depression, and anxiety did not move in lock-step, indicating that they are different and robust constructs. Targeted intervention strategies should be developed for different subgroups.